Factors Related to Nurse Comfort When Caring for Families Experiencing Perinatal Loss. Issue 3 (May 2015) - Rondinelli, June; Long, Kathleen; Seelinger, Connie; Crawford, Cecelia L.; Valdez, Regina
<x xml:space="preserve">Abstract</x> As nurses provide holistic support, their own comfort in caring for parents and families experiencing perinatal loss must be considered. Study results showed that, although education is essential, experience independently predicted comfort in delivering perinatal bereavement care. Evidence from this study promotes the discussion of how nurse educators can structure professional development programs to best transfer the experience and confidence of perinatal nurses who are already comfortable with bereavement care to nurses who are not.